Exploring the potential of digital game-based vocabulary learning among high school students in Selangor - Razali, Nurul Hidayah; Ahmad, Nur Atikah; Nordin, Ahmad Syaamil; Abd Rahman, Siti Fatimah (RSIS International, 2025)
Vocabulary plays a crucial role for students to learn and with the rapid evolution of digital learning, game-based learning, it becomes a new way to allow students to obtain new vocabularies in fun and meaningful learning. This research aims to find the potential of digital game-based vocabulary learning (DGVCL) among high school students in Selangor. The methodology used in this study is qualitative research design which is interview technique. The main findings reveal that DGVCL helps students to have extra practice, motivation, engagement, creates a positive and stress-free learning environment and self-learning. In this kind of environment, students find the lesson to be engaging and exhibit strong motivation making the lesson to be enjoyable which may in turn enhance their vocabulary retention. These findings make the teachers teach effectively in their classroom and make it as a part of teaching vocabulary through digital game-based learning than conventional teaching methods in an English classroom.